The Anxiety and Fear of COVID-19 Pandemic at the First Year in Dentists Working in Specialist Dental Centers - Al-Shatari, Sahar Abdul Hassan; Abu-Nayla, Maryam faez khazaal; Saddon, Abdul Ganni; Hassan, Zinah M; Al- Juboori, Yahiya B H (AL-Kindy College Medical Journal, 2022)
Background: COVID-19 pandemic has influenced all life aspects; Dental staff, like other healthcare providers, may be exposed to COVID-19 as part of their work and its psychological impacts on healthcare workers should not be ignoredObjectives: To assess the anxiety, and fear from COVID-19 pandemic in dentists working in specialist dental centers: sample the Al-Resafa health directorate, and its relation between the anxiety, and COVID-19 fear with some of their demographic variablesSubjects and Methods: A cross-sectional study was conducted on 2nd Jan. to 14th Feb. 2021, by an electronic version of questionnaire through Google-form; the questionnaire was formed based on Mental-Health-American-Organization (MHAO) for anxiety test & the English-Version of the Fear of COVID-19 Scale. Analysis of data by using SPSS, Frequencies, percentages chi-square test had calculated; P-value considered significant if it's ≤0.05.Results: The response rate was 90.43%, most of them aged less than 30 years old, female 356(60.8%), married status 295(50.3%), Rotator 297(50.7%). The study revealed that moderate anxiety 115(19.6%), moderate and mild fear of COVID-19 in 275(46.9%), severe in 120(20.5%) of them. there is a significant relation between gender &anxiety, marital status & No. of children with COVID-19 Fear.Conclusion: One-fifth of dentists had moderate anxiety, and half of them had a mild fear of COVID-19 & one-fifth had a severe fear of COVID-19.